2022
DOI: 10.1093/europace/euac089
|View full text |Cite
|
Sign up to set email alerts
|

Low-voltage area substrate modification for atrial fibrillation ablation: a systematic review and meta-analysis of clinical trials

Abstract: Aims The value of additional ablation beyond pulmonary vein isolation for atrial fibrillation (AF) ablation is unclear, especially for persistent AF. The optimal target for substrate modification to improve outcomes is uncertain. We investigate the utility of low-voltage area (LVA) substrate modification in patients undergoing catheter ablation for AF. Methods This meta-analysis was reported according to the Preferred Reporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Low-voltage areas are just 1 of a multitude of potential additional ablation targets, which includes linear lesion sets, posterior wall isolation, scar encirclement or homogenization, the ligament of Marshall, complex fractionated electrograms, and focal impulse and rotor modulation . Results of prior studies of LVA ablation have been promising from small trials, but a recent larger trial was disappointing . The investigator group has previously reported the results of the STABLE-SR-II trial, which had a similar design to the present study but evaluated persistent rather than paroxysmal AF .…”
mentioning
confidence: 77%
“…Low-voltage areas are just 1 of a multitude of potential additional ablation targets, which includes linear lesion sets, posterior wall isolation, scar encirclement or homogenization, the ligament of Marshall, complex fractionated electrograms, and focal impulse and rotor modulation . Results of prior studies of LVA ablation have been promising from small trials, but a recent larger trial was disappointing . The investigator group has previously reported the results of the STABLE-SR-II trial, which had a similar design to the present study but evaluated persistent rather than paroxysmal AF .…”
mentioning
confidence: 77%
“…In our study, freedom from AF after a single DISPERS procedure was high but many patients suffered from AT within the follow‐up period. Similar to other ablation approaches that involve any form of substrate‐based ablation, DISPERS ablation is considered as “stepwise” where long term arrythmia freedom can only be achieved by sequential ablations 15–17 …”
Section: Discussionmentioning
confidence: 99%
“…Similar to other ablation approaches that involve any form of substrate-based ablation, DISPERS ablation is considered as "stepwise" where long term arrythmia freedom can only be achieved by sequential ablations. [15][16][17] A procedural duration of 182.00 ± 57.13 min is still considered long when compared to standard PVI duration in experienced centers using a HPSD ablation approach. 18,19 This is due to a longer mapping time when analyzing DISPERS areas as well as the subsequent additional ablation time.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis ( 35 ) showed that LVAs modification strategy was superior to traditional ablation strategy, but it was not further explored whether LVAs modification had the same benefit in AF patients with LVAs. Our study further verified that LVAs modification in AF patients with LVAs can further reduce arrhythmia recurrence.…”
Section: Discussionmentioning
confidence: 99%